Spontaneous spoken language : syntax and discourse - Miller, J. E. (James Edward), 1942- (Clarendon Press ; Oxford University Press, 1998)
Jim Miller and Regina Weinert investigate syntactic structure and the organization of discourse in spontaneous spoken language. Using data from English, German, and Russian, they develop a systematic analysis of spoken English and highlight properties that hold across languages. The authors argue that the differences in syntax and the construction of discourse between spontaneous speech and written language bear on various areas of linguistic theory, apart from having obvious implications for syntactic analysis. In particular, they bear on typology, Chomskyan theories of first language acquisition, and the perennial problem of language in education. In current typological practice written and spontaneous spoken texts are often compared; the authors show convincingly that typological research should compare like with like. The consequences for Chomskyan, and indeed all, theories of first language acquisition flow from the central fact that children acquire spoken language but learn written language.